Study on Roof Breakage-Induced Roadway Coal Burst in an Extrathick Steeply Inclined Coal Seam - Sheng-chuan Wang; Lin-ming Dou; Zong-long Mu; Jin-rong Cao; Xu-wei Li (Shock and Vibration)
In view of the coal burst induced by roof breakage in the steeply inclined coal seam (SICS) roadway and its mechanism, a mechanical model was established to investigate the distribution of dynamic and static stresses in the coal seam before and after the breakage of a thick hard roof. The aim of this research is to study failure laws of SICS roadways under the superposition of dynamic load induced by roof breakage and asymmetric static load. For this purpose, response characteristics including acoustic emission (AE), static stress, and acceleration were analyzed by applying different dynamic loads to different horizontal slices with a self-made similarity simulation test apparatus under combined dynamic and static loads. The theoretical model and simulation results were verified by analyzing characteristics of coal burst occurrence in the field, microseismic (MS) events, and tomographic imaging of microseismic waves. The study demonstrates the following: (1) The abutment pressure of the roof plays a dominant role in stress distribution of the coal seam slice before the breakage of the thick hard roof with the stress of the roof roadway (Rr) being obviously higher than that of the floor roadway (Rf). (2) High-energy MS events and AE events are concentrated on the roof side after the breakage of the thick hard roof, and coal bursts are more easily induced by the superposition of high dynamic and static stresses on the roof side. Coal burst in the roadway is jointly determined by dynamic and static stresses. Under the same static stress, response characteristics increase with the rise of intensity of dynamic loads. When dynamic stress is the same, coal burst easily occurs in the roadway with high static stress.